Pengembangan Pengelolaan Dana Desa Terhadap Kesejahtraan Masyarakat Desa Di Kabupaten Konawe Selatan Provinsi Sulawesi Tenggara - Hasjad Hasjad (Jayapangus Press, 2020)
Development of village fund management is very much needed by the community so that it can be enjoyed by all levels of society in the villages. The seriousness of the government in developing villages is evidenced by the start of allocation of the Village Fund budget for 2015. The allocation of the Village Fund is mandated by Law (Law) Number 6 of 2014 concerning Villages and Government Regulation (PP) Number 6 of 2014 concerning Village Funds Sourced from STATE BUDGET. The regulation explained that the administration of the village government adheres to the principle of decentralization and the task of assistance. The principle of decentralization raises village internal funding (Desa APBD), while the principle of co-administration provides an opportunity for Villages to obtain funding sources from the government above it (APBN, Provincial APBD, Regency / City APBD). This study aims to observe what the development of village funds looks like, how they are implemented and the impact of the use of village funds in supporting development activities and community empowerment. The research method used is a qualitative research method that relies on observing places, actors and activities in Konawe Selatan Regency, Southeast Sulawesi Province, which was chosen as a case study. Initial observations show that the Village Fund does not have significant results in improving the welfare of the community. These indications are evident in the welfare of the community which has not improved with the existence of the village fund. Therefore it is necessary to develop a good management of village funds to improve the welfare of rural communities, especially in Konawe Selatan District. The output to be achieved is the scientific publication with ISSN Online and the level of technological Readiness that will be achieved 1-3.